Persepsi Pegawai Terhadap Work from Home di Politeknik Penerbangan Makassar - Wiwik Wahyuningsih, Bernadetta (Politeknik Penerbangan Makassar, 2021)
This study aims to analyze and describe perceptions about work from home in the COVID-19 pandemic. The population of this research is the employees who work at the Makassar Aviation Polytechnic. The sample of this research is the State Civil Apparatus at the Makassar Aviation Polytechnic. The data were obtained by conducting a survey of 91 respondents. This research indicates that the Makassar Aviation Polytechnic ASN is ready, comfortable and productive while implementing WFH in order to break the chain of Covid-19 spread. After the pandemic ends, the Makassar Aviation Polytechnic ASN hopes to carry out activities at its office again because there are several ASNs who do not carry out WFH because their work cannot be carried out from home. The internet network is the biggest obstacle in implementing WFH because during WFH all work depends on the internet network such as coordination, bold teaching and learning activities, internal meetings and with external parties.